Hydroxamic Acids Immobilized on Resins (HAIRs): Synthesis of Dual‐Targeting HDAC Inhibitors and HDAC Degraders (PROTACs). Issue 50 (9th October 2020) - Sinatra, Laura; Bandolik, Jan J.; Roatsch, Martin; Sönnichsen, Melf; Schoeder, Clara T.; Hamacher, Alexandra; Schöler, Andrea; Borkhardt, Arndt; Meiler, Jens; Bhatia, Sanil; Kassack, Matthias U.; Hansen, Finn K.
Abstract: Inhibition of more than one cancer‐related pathway by multi‐target agents is an emerging approach in modern anticancer drug discovery. Here, based on the well‐established synergy between histone deacetylase inhibitors (HDACi) and alkylating agents, we present the discovery of a series of alkylating HDACi using a pharmacophore‐linking strategy. For the parallel synthesis of the target compounds, we developed an efficient solid‐phase‐supported protocol using hydroxamic acids immobilized on resins (HAIRs) as stable and versatile building blocks for the preparation of functionalized HDACi. The most promising compound, 3 n, was significantly more active in apoptosis induction, activation of caspase 3/7, and formation of DNA damage (γ‐H2AX) than the sum of the activities of either active principle alone. Furthermore, to demonstrate the utility of our preloaded resins, the HAIR approach was successfully extended to the synthesis of a proof‐of‐concept proteolysis‐targeting chimera (PROTAC), which efficiently degrades histone deacetylases. Abstract : Hydroxamic acids immobilized on resins (HAIRs) were developed and utilized for the library synthesis of DNA‐alkylating HDAC inhibitors and a proof‐of‐concept HDAC degrader (PROTAC). A hybrid compound based on the pharmacophores of chlorambucil and panobinostat was identified as the most promising chimeric HDAC inhibitor and demonstrated improved anticancer properties compared to the sum of the activities of either pharmacophore alone.